Kdaj naj se oseba z bolečinami v prebavilih odloči za obisk pri osebnem zdravniku? - Petek, Davorina (Farmacevtski vestnik, 2020)
Abdominal pain is a common symptom, which is frequently associated with other symptoms suchas indigestion, early satiety, nausea, bloating in the abdomen, and disturbances in the discharge of faeces. Patients often practice self-medication and self-treatment, while many of them follow the advice of a pharmacist at the pharmacy. The paper briefly presents the characteristics of problems requiring further diagnostics or prescribing medication beyond the scope of self-medication. The intensity and duration of symptoms, signs of alarm, family history, age, general symptoms such as fever, po-liarthralgias, and previous tests are important when deciding whether to visit a doctor. The aim of the paper is a review of gastrointestinal symptoms and patient characteristics requiring a visit to a family doctor.
Keywords: abdominal pain; bolečina v trebuhu; bolezni črevesja; bowel diseases; dispepsija; dyspepsia